Setting Agenda for Leadership Recruitment: A Content Analysis of Media Treatment of Personality and Competence of the 2011 Presidential Candidates - Aniyi, Sunday Aikuirawo (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
This article examines the level of attention print media gave to the personality and the competence of the presidential candidates as compared to their political leverage in their coverage of the events leading to the 2011 presidential election. Agenda Setting Theory (AST) was used to give the paper a theoretical frame. Quantitative research design using Content Analysis (to evaluate three national newspapers) was adopted. The result showed that more attention was devoted to electoral strength analysis than candidates' competence analysis, while the personalities were more reported than their manifestoes. The paper concludes by recommending that the media must always resist the tendency to hunt for stories that tend to concentrate on politicking and intrigues than the competence of the candidates that have come out to contest. The public need to know more than the candidates would be willing to share with the public about themselves and only the media can fill this gap.